Features of Building Control Systems Sub-Locality in Modern Russia - Shestopal, Sergey S.; Lyubashits, Valentin Y.; Astakhov, Victor V.; Pismennaya, Elena E.; Ryazantsev, Sergey V.; Fedulov, Alexander M.; Barsukov, Pavel V. (International Review of Management and Marketing, 2016)
For practical implementation problems of innovative development of territories in the planning period, using the potential of sub-localities, the development of effective management models and schemes require more advanced scientific and methodological base formed on research of modern processes of territorial management in Russia. It remains largely untapped resource cluster forms of coordination and motivation of business activity of economic entities at the sub-regional level. Disputable issues, methodological approaches and the special importance of solving practical problems of improving the system of economic management sub-localities, as well as the relevance of the scientific study of selected issues, led to the choice of the theme of the work, setting its objectives and the formulation of objectives. Keywords: regional economy, locality management system, economic development JEL Classifications: F38; O35; O10